Aesthetic perception in children with molar incisor hypomineralization - Fragelli, C. [UNESP]; Barbosa, T. S.; Bussaneli, D. G. [UNESP]; Restrepo, M.; Cordeiro, R. C.L. [UNESP]; Santos-Pinto, L. [UNESP] (Springer Nature, 2020)
Purpose: To investigate the relationship between aesthetic perception and molar incisor hypomineralization (MIH) in schoolchildren aged 8–12 years. Methods: The study included 467 pupils enrolled in elementary schools. Once authorization was received, the students were examined for DMFT and dmft indexes (WHO criteria), and for MIH (EAPD criteria). The aesthetic perceptions were verified by the Child Perceptions Questionnaire About Tooth Appearance (CQATA), a questionnaire divided into several items, including physical, psychological and social domains; perception about tooth pleasantness, tooth alignment, tooth discoloration and tooth health; and reported pleasant colour. Data analysis was carried out using descriptive statistics, the Chi-square, the Mann–Whitney and the Kruskal–Wallis tests, and linear regression at a significance level of 0.05. Results: The tooth health perception was worse when the child had MIH, and the tooth alignment and tooth discoloration perceptions, when MIH affected the incisors. The number of teeth affected by MIH was associated with higher averages in the tooth discoloration perception. Conclusions: Children with MIH showed more negative perceptions toward tooth health, tooth alignment and tooth discoloration. However, none of the clinically investigated variables negatively impacted the reported pleasant colour question.
Keywords: Child; Dental aesthetics; Oral health; Tooth demineralization